Simulation of gaseous fuel injector geometries of mult holes nozzle by using CNG engine - Muhamad Akhbar Osman, Md. Hashim (2009)
Compressed natural gas (CNG) is the most preferred for fossil fuel substitution. This project is to study simulation of gaseous fuel injector geometries of multi-hole nozzle by using CNG engine. Three main components are focused on this paper. First, the relation between engine speed and injector pressure in achieving stoichiometric airfuel mixture is investigated. Second, relation between valve lift and injector pressure in obtaining stoichiometric air-fuel mixture is investigated. Lastly the quality of air-fuel mixture in engine cylinder is investigated. Stoichiometric air-fuel mixture leads to good drivability, high combustion efficiency, and avoid internal damage on engine parts. In order to achieve stoichiometric air-fuel mixture, the different engine speeds and valve lift are considered and investigated. Therefore, Computational Fluid Dynamics (CFD) method using COSMOS FloWork simulation software is used for this purpose. The simulation of gaseous fuel injector geometries of multi-hole nozzle by using CNG engine is conducted in 1.78mm, 3.55mm, 5.33mm and 7.1mm intake valve lift, and also engine speeds at 2000 RPM, 3000 RPM, 4000 RPM and 5000 RPM. The results are shown; by increasing the engine speed, the injector pressure increases at different valve lift. Valve lift increment will increase the injector pressure for different engine speeds but the injector pressure is constant for valve lift increment from 75 percent to 100 percent. In the best trend air-fuel mixing result, the injected gas fuel and intake air has been mixed spread evenly in combustion chamber.